Pengaruh Dewan Komisaris dan Komite Audit pada Kualitas Laporan Keuangan - Nugrahani, Tri Siwi (AKMENIKA, 2017)
This study aimed to examine the effect of board of directors and the audit committee on the quality of financial reporting. This research was conducted at the company's listing on the Stock Exchange in 2011-2014. The sampling method with purposive sampling and data collection methods with observation. This study tested with multiple regression analysis to test the hypothesis t test with significance of 5 % .